The impact of intensive endurance training on the risk of atrial fibrillation and quality of life in veteran athletes – a literature review - Jurkowska, Klaudia; Stanik, Martyna; Kępa, Adrianna; Bełc, Ewa; Górak, Joanna; Mahoney, Eleonora Y.; Relisza, Agata; Stadnik, Aleksandra; Trzyna , Elżbieta; Gliwa , Anna (Quality in Sport, 2026)
Background: Regular physical activity is a cornerstone of cardiovascular prevention; however, recent evidence points to a "physical activity paradox." Master athletes engaged in long-term, high-intensity endurance sports show an increased incidence of atrial fibrillation (AF). This presents challenges regarding training safety and the quality of life for patients whose identity is tied to sports. Aim: To summarize current knowledge on the link between long-term endurance training and AF risk in master athletes, and to analyze its impact on their quality of life and physical performance. Materials and Methods: A literature review (PubMed, Scopus, Web of Science, 2020–2026) was conducted, including cohort studies, meta-analyses, and ESC guidelines. Fifty-eight relevant references were analyzed. Results: Analysis confirms a "U-shaped" or "J-shaped" relationship between exercise dose and AF risk. Endurance athletes have a 2 to 10 times higher AF risk than sedentary individuals, linked to structural remodeling (atrial enlargement, fibrosis) and autonomic changes. AF significantly reduces quality of life in previously active individuals. Moderate training reduction and early radiofrequency (RF) ablation are highly effective in improving outcomes. Conclusions: Despite arrhythmia risks, the cardiovascular benefits of exercise outweigh mortality risks; however, master athletes require an individualized clinical approach. Education on intensity modification and monitoring psychophysical well-being are key to maintaining high quality of life in these patients.